INDONESIA'S FUTURE ACTING PRESIDENCY: MAINTAINING OR REPLACING THE NEW ORDER LEGACY - Ramadhan, Febriansyah; Widagdo, Setyo; Widiarto, Aan Eko; Susmayanti, Riana (Veritas et Justitia, 2024)
The interim president anticipates the vacancy of the office of president and vice president; Indonesia calls it ‘pelaksana tugas kepresidenan’, which is filled by the minister of home affairs, foreign affairs, and minister of defense. This article explores the two actors (bureaucrats and legitimacy) who become interim presidents in the constitutions of the world's countries. Next, the Indonesian arrangement and accompanying problems in the 1945 Constitution will be reviewed. This article is aided by a doctrinal research method with historical, legislative, and comparative constitutional approaches. Indonesia has its peculiarities compared to the constitutions of world countries because it applies a compound position as interim President adopted from the New Order legal products (Tap MPR VII/1973) without going through a decontextualisation process, so it still applies the old features (bureaucratic actors) with compound/collegial executive positions in the new constitutional structure that seeks to purify the presidential system. In addition, there are conditions that the 1945 Constitution still cannot resolve and that cause paralysis of governance. This article offers one solution—which could alleviate two specific problems simultaneously—and that is to make the Speaker of the House of Representatives (DPR) the acting President of the future.